Fascist modernities : Italy, 1922-1945 - Ben-Ghiat, Ruth (University of California Press, 2001)
This cultural history of Mussolini's dictatorship discusses the meanings of modernity in interwar Italy. The work argues that fascism appealed to many Italian intellectuals as a new model of modernity that would resolve the European and national crises.
Keywords: Fascism and culture -- Italy -- History.; Fascism -- Italy -- History.; Italy -- Politics and government -- 1922-1945.; Italy -- Intellectual life -- 20th century.; Fascisme et culture -- Italie -- Histoire.; Fascisme -- Italie -- Histoire.; Italie -- Politique et gouvernement -- 1922-1945.; Italie -- Vie intellectuelle -- 20e siècle.; HISTORY.; HISTORY -- Europe -- General.; Fascism; Fascism and culture; Intellectual life; Politics and government; Italy; 1900-1999; 20th century.; cultural history.; dictatorship.; economic development.; europe.; european history.; fascism.; fascists.; historical.; history of culture.; history of society.; history students.; human condition.; interwar history.; italian cinema.; italian culture.; italy.; legacy of fascism.; model of modern world.; modern historians.; modern history.; modernity.; mussolini.; national identity.; national traditions.; revolution.; social boundaries.; social movements.; social status.; History